Urban net primary production: Concepts, field methods, and Baltimore, Maryland, USA case study. Issue 4 (20th March 2022) - Sonti, Nancy F.; Groffman, Peter M.; Nowak, David J.; Henning, Jason G.; Avolio, Meghan L.; Rosi, Emma J.
Abstract: Given the large and increasing amount of urban, suburban, and exurban land use on Earth, there is a need to accurately assess net primary productivity (NPP) of urban ecosystems. However, the heterogeneous and dynamic urban mosaic presents challenges to the measurement of NPP, creating landscapes that may appear more similar to a savanna than to the native landscape replaced. Studies of urban biomass have tended to focus on one type of vegetation (e.g., lawns or trees). Yet a focus on the ecology of the city should include the entire urban ecosystem rather than the separate investigation of its parts. Furthermore, few studies have attempted to measure urban aboveground NPP (ANPP) using field‐based methods. Most studies project growth rates from measurements of tree diameter to estimate annual ANPP or use remote sensing approaches. In addition, field‐based methods for measuring NPP do not address any special considerations for adapting such field methods to urban landscapes. Frequent planting and partial or complete removal of herbaceous and woody plants can make it difficult to accurately quantify increments and losses of plant biomass throughout an urban landscape. In this study, we review how ANPP of urban landscapes can be estimated based on field measurements, highlighting the challenges specific to urban areas. We then estimated ANPP of woody and herbaceous vegetation over a 15‐year period for Baltimore, MD, USA using a combination of plot‐based field data and published values from the literature. Baltimore's citywide ANPP was estimated to be 355.8 g m −2, a result that we then put into context through comparison with other North American Long‐Term Ecological Research (LTER) sites and mean annual precipitation. We found our estimate of Baltimore citywide ANPP to be only approximately half as much (or less) than ANPP at forested LTER sites of the eastern United States, and more comparable to grassland, oldfield, desert, or boreal forest ANPP. We also found that Baltimore had low productivity for its level of precipitation. We conclude with a discussion of the significance of accurate assessment of primary productivity of urban ecosystems and critical future research needs.